Manajemen Pengembangan Obyek Wisata Kawasan Kota Lama Semarang - Febrianna Chadijah; Mochammad Mustam; Hesti Lestari (Journal of Public Policy and Management Review, 2015)
The old area in Semarang is one of assets the city of Semarang and a number of the building worth of the high historical. The condition is currently very poor, so it needs special development and management of governmment in doing conservation and revitalization to revive the area. Revitalization area program the old city Semarang proposed by the government the city of Semarang based on the bylaw year 2003 on spatial planning buildings and environments area the old city Semarang. The local regulations in question is an effort to produce guidelines in developing and managing the old city Semarang be a tourist attraction that can be enjoyed within the city of Semarang. This research should be conducted based on the existing problems in the management and the development of its old city Semarang. Problems arise in the form of what factors be a barrier in development and management of old town area to get into an area of tourism in Semarang city. The purpose of this research is to describe the process of management the development of its old city Semarang as a tourist attraction and analyzing the factors an impediment to the case for the government city of Semarang in the development of tourism old town area Semarang. Efforts to answers questions and the purpose of this research by the use of the theory of public administration, public management, public organization and public policy, management and tourism. The writing of this analysis uses the technique of qualitative data descriptive. Based on the results of this research that there are still several problems that is situated on the weakness of coordination between the relevant SKPD that was one of factors that hampers in development and management of old town area Semarang. In addition there are some forms of market not according to rule areas which have been made municipalities to enhance old town area Semarang.